Taxonomy and diversity of Hydrozoa (Cnidaria, Medusozoa) of La Paz Bay, Gulf of California - Mendoza-Becerril, María A.; Estrada-González, Mariae C.; Mazariegos-Villarreal, Alejandra; Restrepo-Avendaño, Luisa; Villar-Beltrán, Rogelio D.; Agüero, José; Cunha, Amanda F. (Zootaxa, 2020)
The Mexican Pacific has been the focus of several research expeditions, with 90 species of hydromedusae and more than 200 species of hydroids recorded for the region. However, only a few of these reports include taxonomic descriptions, hindering inferences of the phylogenetic relationships, species boundaries, and diversity of Hydrozoa in Mexican waters. In this study, we present detailed and illustrated descriptions of new records of hydromedusae and hydroids for La Paz Bay, Gulf of California. We found a total of 16 species comprising 15 genera, with three new records for the Gulf of California (polyps of Antennella secundaria, Bimeria vestita, and Ventromma halecioides), two new records for the Mexican Pacific (medusa of Clytia linearis, polyp of Halopteris violae), and we redescribe Obelia tenuis. We show that the diversity of Hydrozoa in the Mexican Pacific is likely underestimated, and we emphasize the importance of taxonomic and systematic studies of hydroids and hydromedusae in Mexico.